[PP.03.03] ADDITIONAL FACTORS ASSOCIATED WITH LEFT VENTRICLE DIASTOLIC FUNCTION IMPAIRMENT IN PATIENTS WITH MODERATE HYPERTENSION. (September 2016) - Torbas, O.; Sirenko, Y.; Kushnir, S.; Rekovets, O.
Abstract : Objective: Not only hypertrophy but other factors influence diastolic dysfunction (DD) profile that also should be considered. Design and method: We included 154 patients with moderate arterial hypertension (AH) (mean SBP 151, 1 ± 2, 03; mean DBP 93, 12 ± 1, 87), 52, 5% women and 47, 5% men. All patients underwent echocardiography with the definition of left (LAI) and right atrial (RAI) indexes, left ventricular myocardium mass index (LVMMI), mitral valve (MVG) and aortic valve (AVG) gradients, diastolic dysfunction with E/A and E/E', deceleration time (Dt) evaluation, the amplitude of the septal part of mitral annulus motion (Sm), office SBP, DBP, height, weight, BMI, body surface area measurements. According to the results of E/E' ratio patients were divided into two groups-more than 10 (n = 79) and less than 10 (n = 75). Results: Groups did not differ significantly according to theirs height (167, 1 ± 0, 9 vs 169, 6 ± 1, 2 in E/E'>10 vs E/E'<10 respectively), BMI (30, 8 ± 1, 8 vs 29, 6 ± 2, 3 respectively), body surface area (2, 03 ± 0, 03 vs 2, 02 ± 0, 04 respectively) parameters and levels of office SBP (151, 5 ± 3, 8 vs 150, 3 ± 1, 9 respectively) and DBP (92, 4 ± 1, 9 vs 91, 2 ± 2, 2 respectively). In group of patients with E/E'>10 LAI and RAI were significantly higher (30, 2 ± 1, 4 vs 26, 4 ± 1, 2, p = 0, 042), LVMI in these patients was also significantly higher (111, 8 ± 4, 1 vs 97, 9 ± 3, 0; p = 0, 07). There was significantly higher MVG (6, 7 ± 0, 4 vs 4, 7 ± 0, 2; p < 0, 001) and AVG (16, 2 ± 1, 9 vs 11, 5 ± 1, 2; p = 0, 03). The amplitude of mitral annulus motion in these patients was significantly lower (8, 9 ± 0, 3 vs 10, 7 ± 0, 4; p = 0, 001). Dt was significantly higher in E/E'>10 group (274, 3 ± 11, 2 vs 232, 2 ± 11, 5; p = 0, 011). No significant difference in E/A and EF was found. In the main group LAI and RAI correlated significantly with E/E' (r = 0, 24, p = 0, 009 and r = 0, 193, p = 0, 041), moreover, this correlation with LAI remained significant even after correction for LVMMI (B = 0, 2; p = 0, 036). A correlation was also observed for E/E' with MVG (r = 0, 38; p = 0, 001) and AVG (r = 0, 30; p < 0, 001), correlation with MVG was significant after amendment for LAI and EF (B = 0, 35; p < 0, 001). Conclusions: Left ventricular hypertrophy affects the DD formation. However, atrial remodeling has its own independent effect on the DD in patients with AH. Moreover, MVG and AVG were correlated significantly with DF indicators, regardless of EF or left atrium condition.